Influence of environmental factors on the distribution of tree species in the forests of southeastern Mexico. - Cortés-Castelán, José C. (2005)
We studied the relationship between the distribution of tree species and environmental factors in the Sian Ka’an Biosphere Reserve, south-eastern Mexico. Our main objective was to examine how changes in microtopography and edaphic factors influence the distribution of tree species of medium and lowstatured forests. We established 17 plots of 625 m2 and collected data on spatial distribution of individuals with dbh ≥ 5 cm, and the following soil variables: electric conductivity (CE), cationic exchange capacity (CEC), textural class, pH, organic matter (MO), total nitrogen (Nt) and phosphorus availability (P). We used Twinspan to classify the plots and applied indirect (DCA) and direct (CCA) gradient analysis. We found 84 species and 4 433 individuals. MO, texture and CEC varied significantly (p≤0.05) between the high and low parts. DCA and CCA indicated that the species distribution is strongly influenced by the microtopography gradient and the textural class. Using DCA and CCA exclusively on the data of the low parts, two low statured forest types were identified: one characteristic of low zones (soil slightly basic and high percentage of clay), the other surrounded by medium statured forest (soil slightly acid, high CEC, MO and clay).